Answer:
Hi, I believe 1-0.25c is the correct answer.
Step-by-step explanation:
This is because 25% off would mean taking 25 off of a whole amount, which in this case would be one.
Answer:
-1,3i,-3i
Step-by-step explanation:
X^3+x^2=-9x-9
x^3+x^2+9x+9=0
x^2(x+1)+9(x+1)=0 factorize by taking x+1 common factor
(x+1)(x^2+9)=0
x+1=0 then x=-1
(x^2+9)=0 then x=+ 0r - 3i
<span>y = tan^−1(x2/4)</span>
tan(y) = x2/4
sec2(y) = x/2
y′ = xcos^2(y)/2
<span>cos^2(y) = <span>16x2+16</span></span>
<span>y′ = <span>8x/(<span>x2+16)
let u be x2+16
du is 2x dx
dy = 4 du / u
y = 4 ln (</span></span></span>x2 <span>+ 16)
y at x =0 = </span> 4 ln (<span>16) = 11.09</span>
1374 multiplied by 6 would be 8244
:)
Answer:
2.6795
Step-by-step explanation:
Just ask! :)
(✿◡‿◡) HAPPY HOLIDAYS!!!